If Big Firms Need Managerial Innovation, How Much More Do Startups? – The Key Role of Management Control - DIOP, SARA; OUAHRAOUI , Fatima (Revue du contrôle, de la comptabilité et de l’audit, 2025)
In fast-paced entrepreneurial environments, control is no longer the enemy of creativity—it is its unlikely enabler. This study investigates whether management control tools can be considered as forms of managerial innovation in startups, examining how they are adopted, adapted, and reinterpreted within organizations marked by uncertainty, growth, and strategic flux. Drawing on a hybrid methodology that combines a narrative literature review with a systematic review, this research bridges conceptual foundations with empirical insights from peer-reviewed articles indexed in Scopus and Web of Science. The findings reveal that control tools—such as dashboards, budgeting systems, and performance indicators—are increasingly mobilized by startups not just for oversight, but as strategic instruments for alignment, learning, and legitimacy. These tools act as radical innovations when they redefine managerial paradigms, as relative innovations when adopted for the first time, and as incremental innovations when customized through iterative learning. The study underscores the interplay between external institutional pressures and internal agency in shaping these trajectories. By reframing control systems as evolving and context-sensitive innovations, this paper contributes to a renewed understanding of how startups navigate the paradox of structure and flexibility. Keywords : Managerial Innovation; Management Control; Startups; Innovative Business Model; Performance Management.